PENERAPAN KONSEP MAQASHID SYARIAH UNTUK REALISASI IDENTITAS POLITIK ISLAM DI INDONESIA - Novi Rizka Amalia (Dauliyah Journal of Islamic and International Affairs, 2017)
Indonesia is one of Muslim majority country in Asia and the largest Muslim population in the world, even the historical record of Indonesian independence achieved by Muslim fighters. Islamic values colored the formation of a legal basis in Indonesia, but the implementation is a lot of inequality, so the longer the Identity country further away from the basic principle of appropriate early construction. As a democratic country that is based on Pancasila Indonesia should be able to maintain the rights of citizens in accordance with the applicable Norms. Fading Identity Politics in Indonesia make Indonesia increasingly distant from the expectations prosperity aspired. So that reformation of welfare in Indonesia, the implementation of Islamic values and norms needs to be clarified, including the present one maqashid concept of Sharia in Identity Politics, so as to create ideals to realize an Indonesia that have character and can certainly restore the prosperity that has been desirable because basically the nature of Islam itself is a grace for the entire universe.